The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.7438/1584-9341-9-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Treatment for Multiple Inguinal Hernias – Case Report

Abstract: The miopectineal weak area described by Fruchaud is better visualized by laparoscopic approach, and associated occult hernias of this region can be easily diagnosed, either ipsilateral or contralateral. The goal of this paper is to emphasize the less obvious advantages of mini-invasive approach, by a case study of a bilateral hernia (left inguinal hernia and recurrent right inguinal hernia), operated by laparoscopic means using TEP (total extraperitoneal) approach. A femoral hernia without clinical manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The reported results of the differences in hospital stay between the two techniques are very diverse, probably because it depends on various factors such as age, complication rate, postoperative pain, social factors, educational factors, and trust in the surgeon [ 45 , 46 ]. A randomized trial found no significant difference in hospital stay between TAPP and TEP in bilateral inguinal hernia repair [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported results of the differences in hospital stay between the two techniques are very diverse, probably because it depends on various factors such as age, complication rate, postoperative pain, social factors, educational factors, and trust in the surgeon [ 45 , 46 ]. A randomized trial found no significant difference in hospital stay between TAPP and TEP in bilateral inguinal hernia repair [ 22 ].…”
Section: Discussionmentioning
confidence: 99%